Prognostic Value of the Systemic Inflammatory Response Index in Patients Undergoing Radical Cystectomy for Bladder Cancer: A Population-Based Study - Ni, Jinliang; Wang, Keyi; Zhang, Houliang; Xie, Jinbo; Xie, Jun; Tian, Changxiu; Zhang, Yifan; Li, Weiyi; Su, Bin; Liang, Chaozhao; Song, Xinran; Peng, Bo (Frontiers in Oncology, 2021)
Purpose: This study aimed to investigate the prognostic significance of systemic inflammatory response index (SIRI) in patients with bladder cancer (BCa) treated with radical cystectomy (RC) and develop a survival predictive model through establishing a nomogram. Materials and methods: A total of 203 BCa patients who underwent RC were included in this study. The relationship between SIRI and overall survival (OS), disease-free survival (DFS), clinicopathological features were evaluated. The Cox regression analysis was performed to investigate the effect of the factors on the OS and DFS. The results were applied in the establishment of a nomogram. Receiver operating characteristic (ROC) curves, decision curve analysis (DCA), calibration curves were performed to assess the predictive performance and accuracy of the nomogram, respectively. Results: According to the classification of SIRI, 81 patients [No. (%), 39.9] were assigned to SIRI grade 1, 94 patients [No. (%): 46.3] were defined as SIRI grade 2 and the rest of 28 patients [No. (%), 13.8] were divided to SIRI grade 3. Multivariate Cox regression revealed that higher SIRI grade was significantly associated with poor prognosis and served as an independent prognostic factor for OS [Grade 2 vs Grade 1, odds ratio=2.54, 95% confidence interval (CI),1.39-4.64, P=0.002; Grade 3 vs Grade 1, odds ratio=4.79, 95%CI: 2.41-9.50, P<0.001] and DFS [Grade 2 vs Grade 1, odds ratio=2.19, 95% CI, 1.12-4.31, P=0.023; Grade 3 vs Grade 2, odds ratio=3.36, 95%CI, 1.53-7.35, P=0.002]. The ROC and DCA analysis indicated the nomogram based on SIRI contained the better predict performance compared with TNM stage (AUC=0.750 and 0.791; all P<0.05). The ROC analysis showed that nomograms can better predict 3- and 5- year OS and DFS. The calibration curves exhibited significant agreement between nomogram and actual observation. Conclusion: The SIRI as a novel independent prognostic index and potential prognostic biomarker effectively improve traditional clinicopathological analysis and optimize individualized clinical treatments for BCa patients after RC.